Fluid Vibration Analysis of Large-Span Skeletal Membrane Structures under Pulsating Winds - Wei Fu; Haixu Yang; Jie Jia (Advances in Civil Engineering)
To identify the location of the strongest vibration of skeletal membrane structures under pulsating wind and predict the response and damage of the structures. To guide engineering reinforcement, base on the platform of ANSYS Workbench as a platform, the complex skeleton membrane structure is first simplified using the modal fitting method, and the error of the 30th-order frequency of the membrane structure before and after the simplification is calculated to be less than 5% compared to the unsimplified model. Based on the simplified model, the unidirectional coupling and bidirectional coupling methods were compared using the surface averaging wind pressure distribution parameters of the membrane structure. The results show that the extreme value and extreme difference of the averaged wind pressure of the bidirectional coupling are larger than those of the unidirectional coupling under the same wind angle, which verifies the reliability of the vibration analysis of the large-span membrane structure under the bidirectional coupling. By analyzing the wind pressure coefficients at the key measure points, it can be seen that the structure is in unfavorable working condition at the wind angle of 0°–45°. Based on the bidirectional coupling method, the maximum displacement time variation curve, maximum acceleration time variation curve, and maximum equivalent force time variation curve for different wind direction angles are basically the same, and the membrane structure gradually equilibrates with time, and the maximum instantaneous displacement, maximum instantaneous acceleration, and maximum equivalent force all reach the maximum at wind direction angle 30° and the minimum at 90°.